Chaotic Genetic Patchiness in the Highly Valued Atlantic Stalked Barnacle Pollicipes pollicipes From the Iberian Peninsula: Implications for Fisheries Management - Parrondo, Marina; Morán, Paloma; Ballenghien, Marion; Acuña, Jose L.; Aguión, Alba; Arrontes, Julio; Chiss, Juliette; Cruz, Teresa; Fernandes, Joana N.; García-Flórez, Lucía; García-Vázquez, Eva; Geiger, Katja J.; et al. (Frontiers in Marine Science, 2022)
The stalked barnacle Pollicipes pollicipes inhabits rocky shores from the Atlantic coasts Brittany (France) to Senegal. Because of the culinary traditions of southern Europe, stalked barnacles represent an important target species for local fisheries on the Iberian Peninsula. To manage this fishery sustainably, it is therefore important to assess the dynamics of local populations over the Iberian coast, and how they are interconnected at a wider scale using finely tuned genetic markers. In this work, a new enriched library of GT microsatellites for P. pollicipes was prepared and sequenced using Ion TorrentTM Next Gen-Sequencing technology, and 1401 adults and juveniles were sampled in 15 localities of three geographic regions: Galicia and Asturias (both in northern Spain) and southern Portugal. Twenty polymorphic loci arranged in five multiplex PCRs were then tested and validated as new molecular tools to address the spatial and temporal genetic patterns of P. pollicipes. Our results revealed high genetic diversity among adults. However, juveniles were genetically more structured than their adult counterparts, which alternatively displayed much more connectivity among the three studied regions. The lack of spatial genetic heterogeneity in adults may be due to the superimposition of several generations of settlers coming from different geographic origins, which mainly depends on the orientation of residual currents along the coast during reproduction. The genetic differentiation of juveniles may indeed be congruent with Iberian Peninsula hydrodynamics, which can produce chaotic genetic patchiness at small temporal scales due to sweepstake reproductive success, collective dispersal and/or self-recruitment. Remarkably, most of the genetic heterogeneity of juveniles found in this work was located in Galicia, which could represent an admixture between distinct metapopulations or an old refuge for most northern populations. To conclude, high genetic variation in P. pollicipes can lead to the false impression of population panmixia at the Iberian scale by masking more restricted and current-driven larval exchanges between regions. This possibility should be taken into consideration for further specific management and conservation plans for the species over the Iberian Peninsula.